Changes of polyphenols and antioxidants of arabica coffee varieties during roasting - Mestanza, Marilu; Mori-Culqui, Pati Llanina; Chavez, Segundo G. (Frontiers in Nutrition, 2023)
Coffee is the most consumed beverage in the world after water. Multiple benefits are attributed to it in human health due to the presence of antioxidant compounds, whose content depends, among other factors, on the processing conditions of the coffee bean. The objective of this study was to determine the kinetics of polyphenols and antioxidants during the roasting of three varieties of arabica coffee. For this, we worked with varieties of coffee, Catimor, Caturra, and Bourbon, from the province of La Convencion, Cuzco, Peru. The samples were roasted in an automatic induction roaster, and 12 samples were taken during roasting (at 0, 1, 3, 5, 7, 9, 11, 13, 15, 17, 19, and 21 min of roasting) in triplicate. For green coffee beans, titratable acidity, total soluble solids, moisture and apparent density were determined. The change in polyphenol content was determined using the Folin-Ciocalteu method, and antioxidant activity was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis- (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS+) free radical capture technique during roasting. Polyphenol and antioxidant contents increased until minute 5 of roasting and then decreased until minute 20, and in some cases, there were slight increases in the last minute. The model that best described the changes in these bioactive compounds was the cubic model (R2 0.634 and 0.921), and the best fits were found for the Bourbon variety, whose green grain had more homogeneous characteristics. The changes in the relative abundances of nine phenolic compounds were determined using high-performance liquid chromatography (HPLC). In conclusion, roasting modifies phenolic compounds and antioxidants differently in the coffee varieties studied. The content of some phenols increases, and in other cases, it decreases as the roasting time increases. The roasting process negatively affects the bioactive compounds and increases the fracturability of Arabica coffee beans, elements that should be taken into account at the moment of developing roasting models in the industry.